Breast mass as the first sign of metastasis from rectal carcinoma: a case report and review of the literature - Xu, Jiawei; Liu, Chao; Yu, Chengdong; Yu, Tenghua; Fan, Fan; Zhang, Xiaofang; Huang, Chuansheng; Chen, Wen; Sun, Zhengkui; Zhou, Meng (Frontiers in Oncology, 2023)
We present a case report of a 41-year-old woman who developed a left breast mass 18 months after undergoing Dixon rectal cancer surgery. The purpose of this case report is to highlight the possibility of breast metastases in patients with colorectal cancer and emphasize the importance of careful evaluation and follow-up as well as timely and accurate diagnosis and management of the metastatic disease. During the physical examination in 2021, we noted that the lower border of the mass was 9 cm from the anal verge and that it occupied approximately one-third of the intestinal lumen. A pathological biopsy revealed the mass in the patient's intestinal lumen was a rectal adenocarcinoma. The patient underwent Dixon surgery for rectal cancer and received subsequent chemotherapy. The patient had no prior history of breast-related medical conditions or a family history of breast cancer. During the current physical examination, we discovered multiple lymphadenopathies in the patient's left neck, bilateral axillae, and left inguinal region, but none elsewhere. We observed a large erythema of about 15x10 cm on the patient's left breast, with scattered hard nodes of varying sizes.Palpation of the area beyond the upper left breast revealed a mass measuring 3x3 cm.We conducted further examinations of the patient, which revealed the breast mass and lymphadenopathy on imaging. However, we did not find any other imaging that had significant diagnostic value. Based on the patient's conventional pathology and immunohistochemical findings, combined with the patient's past medical history, we strongly suspected that the patient's breast mass was of rectal origin. This was confirmed by the abdominal CT performed afterward. The patient was treated with a